IDENTIFICATION OF MYCOBACTERIUM LEPRAE IN HOUSEHOLD CONTACTS OF LEPROSY PATIENTS IN BONE BOLANGO DISTRICT - Sangit, Putri; Dunggio, Yolan; Nasar (LPPM Universitas Bina Mandiri Gorontalo, 2024)
The purpose of this study was to identify the presence of Mycobacterium leprae and determine the bacterial index (IB) and morphological index (IM) in household contacts of leprosy patients in Bone Bolango Regency. The research method used a descriptive approach with data collection methods through observation, interviews, and laboratory examinations. Samples were taken from household contacts of leprosy patients in two sub-districts with the highest number of new leprosy cases, namely Bone Raya District and Tapa District. The examination was carried out in the laboratory of Toto Kabila Hospital. The results of the study showed that of the five samples studied, one sample showed positive results with a bacterial index (IB) of +3, which means that there were 1-10 acid-fast bacteria (AFB) in one field of view. The morphological index (IM) of the positive sample was 50%. These results indicate the transmission of M. leprae among household contacts of leprosy patients. Conclusion : There is One case positive of the five samples tested . The samples own index bacteria (IB) +3, which indicates the presence of 1-10 BTA germs in One roomy view . On the index morphological (IM) found by 50%. Findings This emphasize importance routine check and detection early For prevent distribution disease leprosy.